Good practice principles in modelling defined contribution pension plans - Kevin Dowd; David Blake (Journal of Risk and Financial Management, 2022)
We establish 16 good practice principles for modelling defined contribution pension plans. These principles cover the following issues: model specification and calibration; modelling quantifiable uncertainty; modelling member choices; modelling member characteristics, such as occupation and gender; modelling plan charges; modelling longevity risk; modelling the post-retirement period; integrating the pre- and post-retirement periods; modelling additional sources of income, such as the state pension and equity release; modelling extraneous factors, such as unemployment risk, activity rates, taxes and welfare entitlements; scenario analysis and stress testing; periodic updating of the model and changing assumptions; and overall fitness for purpose.
Keywords: C15; C18; C63; C68; D14; D91; 330; defined contribution pension plans; PensionMetrics methodology; OECD Roadmap for the Good Design of Defined Contribution Pension Plans; EIOPA Good Practices on Information Provision for DC Schemes; Enabling Occupational DC Scheme Members to Plan for Retirement